Research on the simplified calculation method of non-limit active earth pressure of limited soil mass in adjacent foundation pits - Zhenbo Zhang; Zhengyuan Wang; Fei Xu; Fei Wu; Zhichun Liu; Xiaofan Chen; Jingliang Kang (PLoS ONE, 2026)
This study aims to solve two critical issues in close-proximity foundation pit engineering: the cumbersome calculation process of non-limit active earth pressure for confined soil masses, and the unclear quantitative relationship between earth pressure magnitude and retaining structure displacement. By establishing the coupling relationship among static earth pressure, limit active earth pressure and non-limit active earth pressure, this paper derives analytical expressions for both the intensity and resultant force of non-limit active earth pressure corresponding to five distinct soil failure modes. The proposed theoretical model is validated through systematic laboratory model tests and finite element numerical simulations. Furthermore, the concept of non-limit active earth pressure isograms is introduced, and the influence mechanisms of various engineering parameters on the isogram distribution characteristics are quantitatively analyzed, revealing their inherent nonlinear distribution laws. Finally, a practical simplified calculation method is proposed, which provides a reliable theoretical basis and technical reference for the design and construction of retaining structures in close-proximity foundation pit engineering.